Can Self-Compassion Improve Adolescents Psychological Well-being? - Lutfi Hidayati Fauziah; Miftakhul Izza Rofiqoh (Universitas Negeri Surabaya, 2023)
Individual always prioritizes the achievement of psychological well-being, as well as adolescents who live in Islamic boarding schools also have their own challenges in achieving it. Self compassion is a factor affecting psychological well-being. Self compassion offers a way for individuals to be able to have kindness with their self, mindfull into their life and a sense of common to other individuals, and will see an obstacle in life to be their best friend. The researchers’ aim was to examine the effect of self-compassion on the psychological well-being of adolescents. This study used quantitative research design, with 200 youth as subjects living at the Salaf Islamic Boarding School in Singosari. Data collection used random sampling, using the Ryff Psychological Well Being Scale (RPWBS) (α = 0.869), the Self Compassion Scale (SCS) (α = 0.721). The correlation test technique to see the effect of the variables is linear regression test to test the effect of the two variables. The results give show that self-compassion can have a positive effect on psychological wellbeing in adolescents. F count value > F table value (17.104 > 3.942), r value of 0.289 > r table 0.138, the contribution made by Self-compassion to psychological well-being is 8.4%. These results show that both variables are positively and significantly related.The implication given to this research is that with the significant influence of self-compassion on psychological well-being in adolescents, it is important for adolescents to have good and optimal self-compassion so that they love and care for themselves, understand their own needs, have the strength to face all challenge, so that adolescents can have good psychological well-being that is able to grow, develop, achieve and work optimally. Setiap individu selalu mengutamakan pencapaian Kesejahteraan psikologis (psychological well-being) dalam dirinya, begitupun remaja yang tinggal di Pondok Pesantren juga memiliki tantangan tersendiri dalam pencapaiannya. Self-compassion merupakan salah satu yang mampu mempengaruhi kesejahteraan psikologis. Self- compassion menawarkan cara untuk individu agar mampu melampaui hambatan-hambatan dalam kehidupannya, dengan Self kindness, mindfullness dan a sense of common humanity individu akan memandang sebuah hambatan dalam hidup menjadi kawan terbaik mereka. Tujuan Peneliti ialah untuk menguji pengaruh Self- Compassion terhadap kesejahteraan psikologis pada remaja. Penelitian ini menggunakan design penelitian kuantitatif, dengan subyek sebanyak 200 Remaja yang tinggal di Pondok Pesantren Salaf di Singosari. Pengambilan data menggunakan random sampling, dengan menggunakan skala Ryff Psychological Well Being Scale (RPWBS) (α = 0,869) dan Self Compassion Scale (SCS) (α = 0, 721). Teknik Uji korelasi untuk melihat pengaruh variable ialah uji regresi linear untuk menguji pengaruh kedua variabel. Hasilnya menunjukkan bahwa self compassion mampu memberikan pengaruh yang positif terhadap kesejahteraan psikologis (psychological well-being) pada remaja. Nilai F hitung> nilai F tabel (17,104 > 3,942), nilai r sebesar 0,289 > r tabel 0,138, kontribusi yang diberikan oleh Self compassion terhadap kesejahteraan psikologis sebesar 8,4 %. Hasil tersebut menunjukkan kedua variable berhubungan positif dan signifikan. Implikasi yang diberikan pada penelitian ini ialah dengan adanya pengaruh yang signifikan self compassion terhadap kesejahteraan psikologis (psychological well-being) pada remaja, maka pentingnya remaja memiliki self compassion yang baik dan optimal agar mencintai dan peduli akan dirinya, memahami kebutuhan diri, memiliki kekuatan menghadapi segala tantangan, sehingga remaja bisa memiliki kesejahteraan psikologis yang baik yang mampu tumbuh, berkembang, berprestasi dan berkarya dengan optimal.